Estrogenic activity research of a novel fluorinated bisphenol and preparation of an epoxy resin as alternative to bisphenol A epoxy resin. (November 2018) - Jiang, Hao; Sun, Lin; Zhang, Yurong; Meng, Fanting; Zhang, Wanxi; Zhao, Chengji
Graphical abstract: Highlights: A low estrogenic activity bisphenol (BTFMHQ) and its corresponding epoxy resin (BTFMEP) were synthesized. BTFMHQ presented lower estrogenic activity than commercial bisphenols. BTFMEP showed lower coefficient thermal expansion than DGEBA. BTFMEP exhibited lower dielectric constant (2.59 at 1 MHz) than DGEBA. Abstract: A low estrogenic activity bisphenol 3, 5-bis(trifluoromethyl)phenylhydroquinone (BTFMHQ) and its corresponding epoxy resin (BTFMEP) were synthesized via a multi-step procedure including the Meerwein arylation reaction, and followed by nucleophilic reaction. The chemical structures of two monomers were confirmed by their 1 H NMR spectra. After curing, the properties of this fluorinated epoxy resin were measured and compared with the commercial epoxy resin diglycidyl ether of bisphenol A (DGEBA). As the result, BTFMEP exhibited good dimensional stability, excellent hydrophobic and low dielectric properties. Furthermore, BTFMEP showed a high glass transition temperature of 142 °C and a lower coefficient thermal expansion (CTE = 55.03 ppm/°C) than that of DGEBA (CTE = 60.71 ppm/°C). Moreover, BTFMEP exhibited the contact angle of 99.6°, which satisfied the standard of hydrophobic material. In addition, BTFMEP showed lower dielectric properties than DGEBA, because the introduction of side groups with high fluorine content into the material improved the electronegativity of epoxy material and reduced the polarizability of molecules efficiently. Herein, we believe the novel epoxy resin (BTFMEP) has a wide application prospect as the alternative to DGEBA.